Morfologi, Materialitas, Dan Nilai Pendidikan Rumah Banjar Bubungan Tinggi - Mesyitahsyare Mesyitahsyare; Zulfa Jamalie (CV. SINAR HOWUHOWU, 2026)
The Banjar House with a High Ridge Roof is an important vernacular architectural heritage that reflects the local knowledge of the Banjar people in responding to the environment, social structure, and cultural values. This study aims to examine the morphology, materiality, and educational value of the Banjar House with a High Ridge Roof in Habirau Village, South Hulu Sungai Regency. The research method uses a qualitative approach with a case study design through architectural observation, documentation, interviews, and literature review. The analysis is conducted descriptively and interpretatively. The research results show that the High Ridge Roof House in Habirau Village has key morphological features such as a high ridge roof, stilt structure, hierarchical spatial arrangement, and symbolic ornaments that function both as adaptations to the tropical climate and as social-cultural markers. The building's materiality is dominated by local hardwood with traditional construction techniques, although some parts have undergone substitution with modern materials. In addition to its physical value, this house contains educational values that include manners and etiquette, mutual cooperation, family life, preservation of local culture, as well as environmental education based on local wisdom. This study confirms that the Banjar High-Roof House in Habirau Village is not only historically and architecturally valuable, but also has the potential as a source of contextual learning in efforts to preserve cultural heritage.